Behavioral benefits of GSK-3β inhibition and state-dependent microtubule signatures in the Fmr1-KO mouse - Kealy, John; Callaghan, Charlotte; Freeburn, Aimée; Thornton, Aoife; Greene, Chris; Garrone, Beatrice; Milanese, Claudio; Bianchi, Massimiliano (Frontiers in Neuroscience, 2025)
Glycogen-synthase-kinase-3β (GSK-3β) and microtubule dynamics are implicated in Fragile X syndrome (FXS). We examined behaviors and hippocampal α-tubulin post-translational modifications (PTMs) in Fmr1-KO male mice without and with chronic administration of the GSK-3β inhibitors SB216763 (30 mg/kg, i.p.) and AF3581 (10 mg/kg, i.p.). Fmr1-KO male mice and wild-type (WT) were evaluated in the open field, marble-burying, elevated-plus-maze (EPM), novel-object-recognition (NOR) and three-chamber sociability test (3-CST); acetylated α-tubulin (Acet/Total-Tub) and tyrosinated/detyrosinated α-tubulin (Tyr/Glu-Tub) ratios were then analyzed. Fmr1-KO male showed hyperactivity, excessive marble burying and impaired NOR; Acet/Total-Tub was elevated and Tyr/Glu-Tub reduced vs. WT, indicating reduced microtubule dynamics. In a mixed-sex cohort bred female WT displayed lower Acet/Total-Tub and increased Tyr/Glu-Tub vs. male WT. The Fmr1-KO-associated decrease in Tyr/Glu-Tub was consistent across sexes. FMRP and synaptic markers were also analyzed in this cohort, spinophilin was found increased in both male and female Fmr1-KO. Fmr1-heterozygous females showed no molecular alterations, supporting the protective role of FMRP. Fmr1-KO male mice received vehicle or GSK-3β inhibitors and were tested in behavioral assays followed by α-tubulin PTMs analysis. Daily vehicle injections appeared to abolish baseline differences in hyperactivity, marble burying and α-tubulin PTMs. Under these conditions both inhibitors reduced marble burying. SB216763 normalized social discrimination in 3-CST, while AF3581 only produced a non-significant positive trend. Neither compound altered α-tubulin PTMs. These results show that GSK-3β inhibition has anti-perseverative and pro-social effects in Fmr1-KO male mice. However, behavioral and molecular endpoints, such as α-tubulin PTMs, appear to be sensitive to both genetic background and experimental procedures.